Analisis Ketebalan Lapisan Sedimen Menggunakan Metode Horizontal to Vertical Spectral Ratio (HVSR) di Wilayah Pesisir Kecamatan Moramo Kabupaten Konawe Selatan: - Laode Ihksan Juarzan; Wan Azizah Wan Jafar; La Hamimu Hamimu; Indrawati Indrawati (Jurnal Rekayasa Geofisika Indonesia, 2023)
Research has been carried out in the coastal area of ​​Moramo District, South Konawe Regency. This study aims to determine the value of the distribution of sediment layer thickness. Data collection was carried out using a TDL-303S seismometer at 15 measurement points. Microtremor data were analyzed using the HVSR method (Horizontal To Vertical Spectral Ratio) use software geopsy 3.4.2 to obtain the dominant frequency value (f0) which then determines the value of the wave velocity shear (VS30) to obtain the value of the thickness of the sediment layer (h). The results of data analysis obtained the dominant frequency value (f0) obtained ranged from 1.025 Hz to 14.297 Hz and the wave speed values shear (VS30) obtained from website www.USGS.gov with a range of values ​​ranging from 234.43 m/s to 422.33 m/s. Based on the data obtained, the value of the distribution of sediment layer thickness (h) will be determined. The thickness of the sediment layer in the study area ranged from 6.596 meters to 66.124 meters.